2020
DOI: 10.1021/acsami.9b23516
|View full text |Cite
|
Sign up to set email alerts
|

Employing a Narrow-Band-Gap Mediator in Ternary Solar Cells for Enhanced Photovoltaic Performance

Abstract: Ternary organic solar cells (OSCs) provide a convenient and effective means to further improve the power conversion efficiency (PCE) of binary ones via composition control. However, the role of the third component remains to be explored in specific binary systems. Herein, we report ternary blend solar cells by adding the narrow-band-gap donor PCE10 as the mediator into the PBDB-T:IDTT-T binary blend system. The extended absorption, efficient fluorescence resonance energy transfer, enhanced charge dissociation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…A small energy offset between the LUMO levels of the donor and acceptors (<0.20 eV) is observed, though it has been shown that such a small offset can efficiently drive charge separation in nonfullerene acceptor based bulk heterojunctions. [39][40][41][42] 43 The effective charge transfer between the PCE10 donor and acceptors is confirmed by photoluminescence (PL) spectroscopy (Figure 1b). An obvious decrease in the intensity of the PCE10 fluorescence spectrum upon mixing with acceptors 3a, 3b, and 3c…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…A small energy offset between the LUMO levels of the donor and acceptors (<0.20 eV) is observed, though it has been shown that such a small offset can efficiently drive charge separation in nonfullerene acceptor based bulk heterojunctions. [39][40][41][42] 43 The effective charge transfer between the PCE10 donor and acceptors is confirmed by photoluminescence (PL) spectroscopy (Figure 1b). An obvious decrease in the intensity of the PCE10 fluorescence spectrum upon mixing with acceptors 3a, 3b, and 3c…”
Section: Resultsmentioning
confidence: 86%
“…An energy level diagram compares the IDTT-TBTA acceptors to the donor polymer PCE10 (Figure b), showing the right alignment of the HOMO and LUMO levels of PCE10 with those of the acceptors (Table ). A small energy offset between the LUMO levels of the donor and acceptors (<0.20 eV) is observed, though it has been shown that such a small offset can efficiently drive charge separation in non-fullerene-acceptor-based bulk heterojunctions. …”
Section: Results and Discussionmentioning
confidence: 99%
“…[13] However, the narrow absorption spectra, amorphous morphology, and relatively strong recombination of the photovoltaic materials are hindrances to improve efficiencies of organic photovoltaics (OPVs). To this end, ternary and quaternary strategies [14][15][16][17] have been proposed. Especially, ternary solar cells taking a third component as guest molecules (acceptor or donor materials) have attracted much attention.…”
Section: Doi: 101002/marc202000393mentioning
confidence: 99%
“…In today's diversified field of solar cells, organic solar cells (OSCs) that can be prepared simply by a solution method have attracted attention because of the significant merits of lightweight, low cost, flexibility, and translucent preparation. [1][2][3][4] In recent years, with the emergence of novel high-efficiency organic photovoltaic materials (such as D18, Y6, etc. ), the performance of OSCs has been rapidly optimized.…”
Section: Introductionmentioning
confidence: 99%